Articulating Hip Spacers with a Constrained Acetabular Liner: Effect of Acetabular Bone Loss and Cementation Quality - Grayson T. Glenn; Andrew E. Apple; Simon C. Mears; C. Lowry Barnes; Benjamin M. Stronach; Eric R. Siegel; Jeffrey B. Stambough (MDPI AG, 2023)
Articulating hip spacers for periprosthetic joint infection (PJI) offer numerous advantages over static spacers such as improved patient mobilization, hip functionality, and soft tissue tension. Our study aimed to determine complication rates of a functional articulating spacer using a constrained liner to determine the role of acetabular cementation mantle and bone loss on the need for second-stage surgery. A retrospective review of 103 patients was performed and demographic information, spacer components and longevity, spacer-related complications, reinfection rates, and grade of bone loss and acetabular cement mantle quality were determined. There was no significant difference in spacer-related complications or reinfection rate between PJI and native hip infections. 33 of 103 patients (32.0%) elected to retain their spacers. Between patients who retained their initial spacer and those who underwent reimplantation surgery, there was not a significant difference in cement mantle grade (p = 0.52) or degree of bone loss (p = 0.78). Functional articulating antibiotic spacers with cemented constrained acetabular liners demonstrate promising early results in the treatment of periprosthetic and native hip infections. The rate of dislocation events was low. Further efforts to improve cement fixation may help decrease the need for second-stage reimplantation surgery.